Selected salivary constituents, physical properties and nutritional status in relation to dental caries among 4-5 year's old children (Comparative study) - Noor A Kadoum; Ban A Salih (College of Dentistry/ University of Baghdad, 2014)
Background: Tooth decay is still one of most common diseases of childhood, child's primary teeth are important even though they aretemporary. This study was conducted to assess the physiochemical characteristic of saliva among caries experience preschool children and compared them with caries free matching in age and gender. Then an evaluation was done about these salivary characteristics to dental caries and evaluated the relation of body mass index to dental caries and to salivary variables. Materials and method: After examination 360 children aged 4-5 years of both gender. Caries-experiences was recorded according to dmfs index by (World Health Organization criteria 1987) during pilot study children with caries experience was divided in to three groups according to decay fraction of decay missing filled surfaces index .Mild with decay surfaces13 and select thirty children with moderate caries experience and compared with thirty caries free children decay missing filled surfaces=0 match in age and gender. Nutritional status of each child was assessed by measuring weight and height to calculate body mass index. Unstimulated saliva collected from sixty child under standardized condition and potential hydrogen and flow rate were measured. Total antioxidant concentration, total protein, calcium, inorganic phosphorus, zinc and copper were measured. Results: Statistically highly significant differences were found in concentration of salivary calcium and inorganic phosphorus between caries-experience and caries free children with higher mean value among caries free group. Statistically significant differences were found in concentration of salivary zinc between groups. Statistically non-significant differences were found in concentration of salivary total antioxidant, total protein, copper and body mass index between caries experience and caries free groups.Salivary flow rate and PH showed statistical non-significant differences between groups. Positive non-significant correlation was found between dmfs index, (ds) fraction of dmfs index and salivary flow rate, total antioxidant and negative correlation with salivary PH, total protein, calcium, phosphorus, zinc and copper. Positive a non-significant correlation was found between BMI, salivary flow rate, PH, total antioxidant, zinc and copper while a negative weak correlation found with dmfs, ds fraction of index and salivary total protein, calcium and inorganic phosphorus in caries experience group. Furthermore a non-significant positive correlation was found between BMI, salivary flow rate, PH, total antioxidant inaddition to that negative weak correlation was found with salivary total protein, calcium inorganic phosphorus, zinc and copper among caries free group. Conclusion: The findings of the present study showed that inorganic components of saliva play an important role in reminerlization of incipient caries and there is an inverse association between body mass index and dental caries.